Comparison of the quality of life of patients with mandibular third molars and mild pericoronitis treated by extraction or by a periodontal approach. Issue 2 (February 2020) - Yurttutan, M.E.; Karaahmetoğlu, Ö.; Üçok, C.; Bağış, N.
Abstract: We have evaluated and compared the outcomes after conservatively treated and surgically managed third molars in patients with mild pericoronitis at the first, third, and sixth postoperative months, and we rated patients' quality of life (QoL) using the Oral Health Impact Profile-14 (OHIP-14) index. Of the 128 patients who were originally assessed as eligible we studied 100 patients who fulfilled the protocol, being diagnosed with mild pericoronitis that affected the third molar teeth and who were followed up for six months. Fifty were treated by the periodontal approach and 50 by extraction of third molars. Their oral health-related QoL was assessed using the OHIP-14 index on a personal assessment question form and then repeated at the first, third, and sixth months. The data were analysed using the Mann Whitney, Friedman's, and Wilcoxon's test, as appropriate. There was a significant difference between the total OHIP-14 scores at different time points (p < 0.0001). In both groups the three postoperative total OHIP-14 scores were significantly lower than the baseline score, and we noted a further decrease in OHIP-14 scores in the surgical treatment group. Periodontal treatment of mandibular third molar teeth may effectively reduce (but does not eliminate) symptoms, whereas tooth extraction seems to be more effective at the long term.